A busca do sensível: impressões visuais, improvisações artísticas e composições históricas - (:unkn) unknown (Universidade Federal de Goiás, 2018)
Thinking about the relationship between art and history is a theme that has guided many researchers. The abstractionism of Wassily Kandinsky (1866-1944) poses a challenge to the historiographic process. Starting from this challenge, I seek in this research to understand the Russian abstractionism of Kandinsky, through the history. His works are the source that unveil the subjective universe that permeates artistic productions in the late nineteenth and early twentieth centuries, characterizing Modern Art. The use of abstractionism as a source has guided us to new readings of historical events such as the First World War and the Russian Revolution. This research is the attempt to understand the search for a new sensibility, in the context of post-revolution Russia. Art is therefore the path to understanding, history guides, in this sense were selected works (paintings and writings) of the painter, from the period 1910 to 1921, from his first abstract production to his compositions.
The search of the sensitive one: visual impressions, artistic improvisations and historic compositions
Keywords: Abstracionismo; Arte; História; Arte abstrata; Sensibilidade; Abstractionism; Art; Story; Abstract art; Sensitivity; CIENCIAS HUMANAS::HISTORIA